FORMULASI DAN UJI EVALUASI PASTA GIGI CANGKANG TELUR BEBEK YANG MENGANDUNG KALSIUM KARBONAT DENGAN VARIASI KONSENTRASI XANTHAN GUM - Ghiffari, Habibie Deswilyaz; Fitrya, Dessy; Sari, Diani Mega; Rushd, Ibnu (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Duck egg shells are an organic waste that is rich in calcium carbonate (CaCO?) and has the potential to be used as a natural abrasive in toothpaste preparations. This research aims to formulate toothpaste using duck eggshell powder as a source of calcium carbonate and evaluate the effect of varying concentrations of xanthan gum as a thickening agent on the physical quality of the resulting toothpaste. This research is experimental. Formulations are made with varying concentrations of xanthan gum, namely 0.5%, 1%, 1.5% and 2%. Evaluation of the preparation includes organoleptic tests, homogeneity, pH, viscosity, cycling test, stress test, long-term stability, and foam tests which are analyzed descriptively. The research results showed that all formulas produced toothpaste that met organoleptic, homogeneity and pH requirements (4.5–10.5). Increasing the concentration of xanthan gum affects viscosity. The formula with a xanthan gum concentration of 2% had the highest viscosity, while the formula with a concentration of 0.5% showed a lower viscosity. The foam test showed that the four formulas were able to produce foam with sufficient volume. In conclusion, formula 2 is a good, stable formula, and has the potential to be developed as a duck egg shell toothpaste preparation.